SRATEGI KOMUNIKASI MORNING BRIEFING DALAM MENINGKATKAN PRODUKTIVITAS DAN KOLABORASI TIM DI LINGKUNGAN BPJS KETEGAKERJAAN KANWIL SUMBAGSEL - Muhammad Haffizd (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This study raises the morning briefing communication strategy in increasing productivity and team collaboration within the BPJS Ketenagakerjaan South Sumatra Regional Office, which aims to find out how important the morning briefing is in the BPJS Ketenagakerjaan environment in the South Sumatra Regional Office. This study aims to evaluate the communication strategies used in morning briefings within the BPJS employment environment at the South Sumatra regional office. We conducted surveys and observations of staff and employees over a 45 day period to identify the most effective types of communication in conveying important information. The results show that the use of technology-based methods in morning briefings, such as the use of dedicated mobile applications, can increase communication effectiveness and reduce misinformation.